Perancangan Sistem Informasi Pelayanan Klinik Citra Utama Berbasis Web Dengan Metode Extreme Programming - Muhamad Arsyah Rahmatullah (Institute of Information Technology and Social Science (IITSS), 2020)
Information development is very fast due to technological advances is one of the most important factors in data processing. Citra Utama Clinic is one of the clinics in the 7 Ulu area of Palembang. Citra Clinic provides a variety of health services. To provide maximum service, a health service information system is needed. This research develops an information system for image clinical services using the Extreme Programming method. This research has produced an information system that can help the health service process and has been tested with black box testing techniques.